"Who Doesn't Think about Technology When Designing Urban Environments for Older People?" A Case Study Approach to a Proposed Extension of the WHO's Age-Friendly Cities Model. - Marston, Hannah R.; Hoof, Joost van (MDPI, 2019)
The World Health Organization (WHO) strives to assist and inspire cities to become more "age-friendly", and the fundamentals are included in the Global Age-Friendly Cities Guide. An age-friendly city enables residents to grow older actively within their families, neighbourhoods and civil society, and offers extensive opportunities for the participation of older people in the community. Over the decades, technology has become essential for contemporary and future societies, and even more imperative as the decades move on, given we are nearly in our third decade of the twenty-first century. Yet, technology is not explicitly considered in the 8-domain model by the WHO, which describes an age-friendly city. This paper discusses the gaps in the WHO's age-friendly cities model in the field of technology and provides insights and recommendations for expansion of the model for application in the context of countries with a high human development index that wish to be fully age-friendly. This work is distinctive because of the proposed new age-friendly framework, and the work presented in this paper contributes to the fields of gerontology, geography urban and development, computer science, and gerontechnology.
Keywords: Stadtplanung; Alter Mensch; Stadtbevölkerung; Stadtdesign; Technologie; Digitalisierung; Assistenzsystem; Roboter; Fußgängerverkehr; Barrierefreiheit; Nahversorgung; Automatisierung